Organic Amendments and Sampling Date Influences on Soil Bacterial Community Composition and Their Predictive Functional Profiles in an Olive Grove Ecosystem - Laura L. de Sosa; Beatriz Moreno; Rafael Alcalá Herrera; Marco Panettieri; Engracia Madejón; Emilio Benítez (Agriculture, 2021)
A collapse of soil microbial diversity, mainly due to chemical inputs, has been reported to lead to the degradation of conventional agroecosystems. The use of compost from urban and agricultural waste management, in order to achieve a net gain in the storage of C, is an adequate management of agricultural soils, especially in rainfed conditions. However, the great variability of composts of different maturity and origins and of the soils to which they are added limits the ability to predict the impact of these amendments on the dynamics of soil microbial communities. This study was designed to gain insights on the effect of exogenous organic matter management on the soil bacterial community and its contribution to key functions relevant to agricultural soils. To achieve this, two different types of compost (alperujo or biosolids composts) at two doses were used as soil amendments twice for 3 years in a rainfed olive grove ecosystem. A metagenomic analysis was carried out to assess the abundance and composition of the soil bacterial communities and predicted functions. We only detected a minor and transitory effect on the bacterial abundance of the soil, the structure of the community and the potential functions, less related to the dose or the type of compost than to seasonal variations. Although the result suggests that the soil bacteria were highly resilient, promoting community stability and functional resilience after the addition of the two composts, more efforts are necessary to assess not only the resulting soil microbial community after organic fertilization but the intrinsic microbial community within the organic amendment that acts as an inoculum, and to what extent the changes in its dose could lead to the functionality of the soil.